Dual Analysis of Loss to Follow-up for Perinatally HIV-Infected Adolescents Receiving Combination Antiretroviral Therapy in Asia - Adam W. Bartlett (2020)
© 2019 The Author(s). Published by Wolters Kluwer Health, Inc. Background:Perinatally HIV-infected adolescents (PHIVA) are an expanding population vulnerable to loss to follow-up (LTFU). Understanding the epidemiology and factors for LTFU is complicated by varying LTFU definitions.Setting:Asian regional cohort incorporating 16 pediatric HIV services across 6 countries.Methods:Data from PHIVA (aged 10-19 years) who received combination antiretroviral therapy 2007-2016 were used to analyze LTFU through (1) an International epidemiology Databases to Evaluate AIDS (IeDEA) method that determined LTFU as >90 days late for an estimated next scheduled appointment without returning to care and (2) the absence of patient-level data for >365 days before the last data transfer from clinic sites. Descriptive analyses and competing-risk survival and regression analyses were used to evaluate LTFU epidemiology and associated factors when analyzed using each method.Results:Of 3509 included PHIVA, 275 (7.8%) met IeDEA and 149 (4.3%) met 365-day absence LTFU criteria. Cumulative incidence of LTFU was 19.9% and 11.8% using IeDEA and 365-day absence criteria, respectively. Risk factors for LTFU across both criteria included the following: age at combination antiretroviral therapy initiation <5 years compared with age ≥5 years, rural clinic settings compared with urban clinic settings, and high viral loads compared with undetectable viral loads. Age 10-14 years compared with age 15-19 years was another risk factor identified using 365-day absence criteria but not IeDEA LTFU criteria.Conclusions:Between 12% and 20% of PHIVA were determined LTFU with treatment fatigue and rural treatment settings consistent risk factors. Better tracking of adolescents is required to provide a definitive understanding of LTFU and optimize evidence-based models of care.